An Empirical Study on the Drivers of Sustainable Consumption Among Muslim Generation Z: The Role of Islamic Values - Ningsih, Ekawati Rahayu; Noor, Sufiana (EQUILIBRIUM, 2025)
This study investigates the influence of Green Marketing Practices (GMP), Environmental Issues (EI), and Green Consumer Identification (CI) on Consumer Sustainable Behavior (CSB) among Muslim Generation Z, proposing Islamic Values (ISV) as a mediating factor. While previous research on this demographic suggests that traditional green marketing and environmental concern may not effectively translate into sustainable action, a gap remains in understanding the role of religious ethics as a bridge to behavior. Using a quantitative design, Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to survey data collected from 268 Muslim Gen Z respondents in Central Java Province, Indonesia, to test the direct and indirect structural relationships. The results established that GMP directly promotes CSB and significantly strengthens ISV. Crucially, ISV emerged as a strong positive predictor of CSB confirming its significant mediating role and highlighting the importance of religion-based values in translating stimuli into action. Conversely, EI and CI did not directly influence CSB, nor did CI significantly affect ISV. This underscores the central role of Islamic values as a primary driver of sustainable consumption in this cultural context. The findings extend sustainability marketing theory by centering religious values in consumer decision-making and practically suggest that campaigns should align with Islamic ethical teachings to effectively translate marketing and awareness into concrete sustainable consumer behavior.